Assessing soil physicochemical properties after shifting cultivation for upland rice in Kampung Kiding, Padawan - Wong, Ruth Wen Ting (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Land use management is a growing importance to ensure the future sustainability of natural resources. Degradation of soil system from affected shifting cultivation is a matter of great concern in terms of loss of a non-renewable resource. The soil properties of natural forest and secondary fallow forest were studied to assess the effect of shifting cultivation for upland rice cultivation on the soil properties in the upland areas in Sarawak, Malaysia. This study will be carried out at Kampung Kiding, Padawan. Surrounded by large area fallow lands and patches of agricultural farmlands, the topography in the area consisted of steed slopes with high elevation located at 1,300 m above sea level. Soil samples were collected from 3 different stages of secondary forest namely: 50 years, 20 years and 5 years after upland rice cultivation. Soil samples were also collected from natural forest as baseline information of the original soil properties in the area. The principle component of soil properties analysis was classified into 3 components: soil texture and organic matter content, soil acidity and ion exchange capability and nitrogen availability. Contrary to previous belief where shifting cultivation damages the nutrients in the natural forest, the burning activity of the topsoil and plant as well as tilling activities actually contributes more nutrients to the soil and these nutrients are essential to assist in plant growth. Results from the study shows due to the topography of the area, even with long fallow period the pool of nutrient contributed by the burning activities and also topsoil tilling eventually gets eroded away or leached deeper into the soil horizon and will not be as readily available for plant uptake. Addition of fertilizer at the right time and with proper management this land can be moderately improved under careful management. However further removal or clearing of land in the area should be discouraged as any further disturbances to the vegetation cover in the area will increase land degradation where the time period for recovery will be long.